2012
DOI: 10.4103/0972-5229.106499
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile, species-specific severity grading, and outcome determinants of snake envenomation: An Indian tertiary care hospital-based prospective study

Abstract: Objective:We undertook this study to assess the clinical profile and outcome determinants of different snake envenomation as well as to assign species-specific severity grade to different cases based on clinico – laboratory evidence scale.Materials and Methods:A prospective clinico – epidemiologic evaluation for outcome determinants of snakebite envenomation was carried out based on a clinico – laboratory severity grading scale, among 76 patients over a period of 2 years, in a tertiary care hospital in souther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 16 publications
5
36
0
Order By: Relevance
“…The male preponderance observed in our study and the age group affected is in close correlation with studies conducted at other centers 4,5 .This may be attributed to their lifestyles involving outdoor activities or occupation as farmers 6 . Most bites in our study were observed during the months of May to November which represents the monsoon.…”
Section: Discussionsupporting
confidence: 90%
“…The male preponderance observed in our study and the age group affected is in close correlation with studies conducted at other centers 4,5 .This may be attributed to their lifestyles involving outdoor activities or occupation as farmers 6 . Most bites in our study were observed during the months of May to November which represents the monsoon.…”
Section: Discussionsupporting
confidence: 90%
“…4,12,13 This could possibly be due to the social behaviour of men as the dominant earning member of the family working out-doors. Of the patients, 69.33% were domiciled in rural areas with a rural: urban ratio of 2.3: 1 similar to other studies reported.…”
Section: Discussionmentioning
confidence: 99%
“…Of the patients, 69.33% were domiciled in rural areas with a rural: urban ratio of 2.3: 1 similar to other studies reported. 12,13 Higher incidence in rural areas can be attributed to farming as an occupation, the habit of walking barefoot and thatched unprotected households. The site of bite was predominantly in the lower limb (80%) while one person had bite in the face.…”
Section: Discussionmentioning
confidence: 99%
“…This can serve as an indication for further research in elucidating the pathology of krait bite induced nephrotoxicity. Regarding the management of krait bite, polyvalent serum still remains the mainstay of therapy (Bawaskar & Bawaskar, 2015;Saravu et al, 2012;Robed Amin et al, 2014;Warrel, 2010).There may be need for organ specific system support for better results. Clinicians should be aware of these conditions while treating cases of krait bite.…”
Section: Discussionmentioning
confidence: 99%
“…Severe envenomation leads to rapid respiratory failure and death. A hospital based study revealed maximum mortality and severity in krait (60%) followed by cobra (13.33%) and viper (8.9%) envenomation (Saravu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%